Planting Seeds in Literary Narrative - Anne W. Anderson (Names, 2022)
On the surface, Yangsook Choi’s The Name Jar (2001) is a simple story of a very young immigrant girl who considers changing her name so her new classmates will like her.  Embedded within the story, however, are key onomastic concepts and questions: What are names? Who decides our names and how? Can we choose different names for different contexts and should we? If we change our names, does who we are change? I revisit scholarly conversations about onomastic theory and discuss narrative as a means of knowing. I draw on Nikolajeva’s (2003) work in narrativity, that is, the ways in which the narrative encourages or discourages deeper thought about the implications of the text. Using analytic reading strategies, I demonstrate how Choi’s uses of verbal and visual narrative devices give the story depth and create space for readers, including scholars, to parse out and ponder onomastic concepts and questions for themselves.